ASSESSING THE BENEFITS OF HAVING A SPECIALIST PAEDIATRIC PHARMACIST AND PHYSIOTHERAPIST IN THE COMMUNITY TO IMPROVE CHILDHOOD ASTHMA OUTCOMES. Issue 9 (17th August 2016) - Lilley, Andrew; Turner, Leanne
Abstract : Introduction: The local Clinical Commissioning Group has funded an innovative one-year pilot project to assess the value of providing specialist paediatric pharmacist and physiotherapist support direct to families and health care professionals (GP's, community pharmacists, practice nurses etc.) regarding asthma in the primary care setting. Currently no such support is provided within community setting by physiotherapy or pharmacy. Methods: Joint holistic reviews by the clinical specialist physiotherapist and specialist paediatric pharmacist were performed in the patient's home environment or school. The review involved a thorough respiratory review and in-depth medication optimisation review ensuring patients were on appropriate regimes and using devices appropriately. Specifically, if an inhaler was indicated a device that the patient was comfortable using was chosen. Furthermore, parents, patients, teachers and school support workers were counselled on how to self manage asthma exacerbations. In order to review benefits patients answered the five question asthma control test (score out of 25), a standardised quality of life questionnaire (score out of 92) and hospital admissions were monitored. Results: At the six-month stage of the project a total of 42 patients had been reviewed and followed up by the project. During the review period there was a total of 1 hospital admission and 1 attendance to the accident and emergency, this is in comparison to the 8 hospital admissions and 47 accident and emergency attendances with this group of patients in the same period the previous year. All patients had an improvement in outcome measures. The average improvement in asthma control test after intervention was 7 points (30%) and a 30% increase in QoL score. We found that symptomatic children had poor FEF25-75 values (<80%) indicating poor lower airways function possibly due to poor drug deposition. After interventions these scores returned to normal limits (>80%). Compliance to medications regimes was noted to be improved after optimisation. Conclusions: It can be clearly seen that joint multidisciplinary reviews by physiotherapy and pharmacy can help improve the outcomes of asthma patients. The joint review of inhaler technique in particular was key. Pharmacy services will tend to concentrate on the use of the device itself whereas physiotherapy monitor the strength and depth of breathes taken. It is well known that good drug deposition is key to the success of inhaled medications. By combining pharmacy and physiotherapy both the use of the device and breathing patterns were optimised both contributing to better drug deposition and improved FEF 25–75% reading. Optimisation of medication was also vital. By ensuring the patient was happy with the device they were using and that it had little negative impact on their daily routine compliance with medications was increased. At the six month stage of the pilot this aspect has proven vital to outcomes in asthmatic patients.